Efektivitas Program Penyiapan Kehidupan Berkeluarga bagi Remaja di Kecamatan Bojonggambir - Budiman, Tuteng (CV. Publikasi Indonesia, 2022)
The problem that arises is that the effectiveness of the program for preparing family life for teenagers in the bojonggambir sub-district has not yet been achieved, including the number of young marriages that are still fairly large, the sources of the religious affairs office in the bojonggambir sub-district, the divorce rate is still very high. There are still many cases of maternal mortality and infant mortality rates, the level of education in family life is still lacking, understanding of family planning programs and delays in the age of marriage are still minimal. The purpose of this study was to determine the effectiveness of the family life preparation program for adolescents in the bojonggambir sub-district. The methods used in this research are: descriptive method with a qualitative approach that is descriptive as a human instrument to determine the focus of the research. The results of the study stated that the effectiveness of the program for preparing family life for teenagers in Bojonggambir sub-district had not been achieved due to not fully implementing effectiveness measures, including the size of the integration program. Then it was concluded that the improvement of human resource capabilities had been carried out although not optimally, the overall parameters were still not optimal, the facilities and infrastructure in the implementation of the family life preparation program for teenagers were not optimal, they still used makeshift facilities, honorariums for implementers.